Biblia jako źródło do badań nad kontaktami handlowymi świata grecko-rzymskiego z południową i wschodnią Azją - Modzelewski, Szymon (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
The Bible mentions several luxury goods (sapphire, emerald, carnelian, topaz, silk, ivory, spikenard, cinnamon, amomum) that were imported by the Roman Empire from South and East Asia via various routes during the 1st-4th centuries CE. The list of goods that appear in the pages of the New Testament testifies to the sound understanding of economic realities that were displayed by the biblical authors and corresponds to the knowledge of Rome's trade contacts with Asian countries.
Keywords: Bible; Roman empire; India; Asia; trade; sapphire; emerald; carnelian; topaz; Silk; ivory; cinnamon; amomum; spikenard